Implementasi Pendidikan Multikultural melalui Ekstrakulikuler Seni Tari sebagai Upaya Menumbuhkan Toleransi dan Apresiasi terhadap Keberagaman di SMAN 5 Mataram - Al Humairah Tsaniatul Fallah; Baiq Syakila Dwi Satria; Yolanda Alfira Febriana; Anggun Febriyanti; Aqillah Deani Alfarosa (Multikultural: Jurnal Ilmu Sosial, 2026)
The purpose of this study is to understand the implementation of multicultural education through traditional dance extracurricular activities as an effort to foster tolerance and appreciation of diversity at SMAN 5 Mataram. The data collection technique in this study was by direct interviews with 3 informants. The results of the study showed that the implementation of multicultural education through traditional dance extracurricular activities at SMAN 5 Mataram was effective in fostering tolerance and appreciation of diversity through collaborative practice and interaction between students. The conclusion in this study is that traditional dance extracurricular activities at SMAN 5 Mataram are effective in implementing multicultural education by fostering tolerance, cooperation, and appreciation of student culture. School and supervisor support are the main factors for success, while limited time, practice space, and differences in student character are obstacles. Overall, this activity contributes positively in forming multicultural attitudes in the school environment. To obtain more information, researchers conducted interviews with 3 informants, namely the head of the dance extracurricular activity, an art teacher, and a PPKn teacher.